Novel Leu-Val Based Dipeptide as Antimicrobial and Antimalarial Agents: Synthesis and Molecular Docking - Ezugwu, James A.; Okoro, Uchechukwu C.; Ezeokonkwo, Mercy A.; Bhimapaka, China R.; Okafor, Sunday N.; Ugwu, David I.; Ekoh, Ogechi C.; Attah, Solomon I. (Frontiers in Chemistry, 2020)
Abstract The increase of antimicrobial resistance (AMR) and antimalarial resistance are intricate and severe health issue nowadays as many of microbial strains had become resistant to the available antibiotics. For discovery of new compounds dipeptide-carboxamide derivatives are chosen as they are well known for their wide range of biological activities such as antimicrobial, antiinflammatory, and antioxidant activities. The condensation reaction of substituted benzenesulphonamoyl pentanamides with the unprotected dipeptides in the presence of peptide coupling reagents gave the targeted products (8a-j).The in silico studies predicted better interactions of compounds with target protein residues and a higher dock score in comparison with standard drugs. The in vivo antimalarial studies showed that almost all the synthesized compounds had good antimalarial property. Compounds 8a, 8b, 8d, 8e, 8g, 8h, 8i, 8j with (43.30–61.90% inhibition) were active compared with the standard drug (with 67% inhibition). Compound 8j was the most potent antimalarial agent with (61.90% inhibition) comparable with 67% inhibition for Artemisinin. In the in-vitro antimicrobial activity, compounds 8a and 8b (MIC 0.6 mg/mL) was most potent against S. aureus, compound 8a, 8b, and 8j (MIC 0.3 mg/mL) was the most active against B. subtilis, compound 8b (MIC 0.5 mg/mL) was most active against E.coli while 8a, 8b and 8d was the most active against S. typhi. Compounds 8c and 8h (MIC 0.8 mg/mL) each were the most active against C. albicans, while compound 8b (MIC 0.7 mg/mL) was most active against Asp. niger.